Determinants of farmland degradation among farming households in West Guji Zone, Ethiopia - Mengistu Bululta; Haile Tamiru; Tariku Ayele (Cogent Economics & Finance, 2022)
This paper aimed to examine the determinants of farmland degradation in the West Guji Zone. The study employed data collected in 2020 from a sample of 385 farm households selected using a simple random sampling technique. An ordered probit model was run to examine the association of explanatory variables with the severity of farmland degradation. Farm plot assessment results indicate that most farm plots were categorized as slightly degraded, followed by moderate, non-degraded, and severe degradation statuses. The study indicated that the main causes of farmland degradation were intensive cultivation without fallow, deforestation, high precipitation, overgrazing, steep slopes, and wind. The ordered probit results revealed that age of household heads, number of plots, and slope of the farmland positively and significantly influenced the severity of farmland degradation, while sex of household heads, soil conservation status, family size, education, land-to-labor ratio, and extension contact were negatively and significantly associated with the severity of farmland degradation. Therefore, the study suggests the provision of training to farming households, promotion of cost-effective modern feed resources and homemade biogas, implementation of a participatory management approach, scaling-up existing land management practices, ensuring the sustainability of natural resource use, and a close linkage between farmers and extension agents to minimize farmland degradation.
Keywords: 330; deforestation; extension contact; Farmland degradation; overgrazing; participatory approach; soil conservation